CONTROLLING MODEL THE SPREAD OF HIV/AIDS AMONG IDUs (INJECTING DRUG USERS) WITH NEP (NEEDLE EXCHANGE PROGRAM) - Mahuda, Isnaini
The spread of HIV/AIDS among IDUs (Injecting Drug Users) has become a global problem that need to be overcome seriously. Sharing needles among IDUs is a major factor in raising the endemic HIV/AIDS. NEP (Needle Exchange Program) as one of the Harm Reduction Program distribute sterile needle to IDUs in order that they can still inject safely. Model of spread of HIV/AIDS among IDUs involving the NEP intervention as a control is discussed in this thesis. This model consists of nine compartments that are classified into seven IDUs compartments namely susceptible (non-treatment and treatment), exposed (non-treatment and treatment), infected (non-treatment and treatment), AIDS and two needles compartments. Disease-free and endemic equilibrium points of the model are obtained from model analysis. Basic reproductive ratio is derived from the spectral radius of the Next Generation Matrix (NGM), but in this case it is impossible to determine analytically. At the end, numerical simulation is performed to find out the dynamics of IDUs population which infected by HIV/AIDS. From the numerical simulation, it is show that by increasing the rate of susceptible and exposed IDUs to enter NEP more effective on reducing the spread of HIV/AIDS among IDUs.